Is Gangliocytic Paraganglioma Designated as a Subtype of Composite Paragangliomas and Originated From Pancreas Islet? A Case Report and Review of Literature - Li, Jing; Wang, Lu-Ping; Zhu, Pei-Shuang (Frontiers in Endocrinology, 2022)
Gangliocytic paraganglioma (GP) is quite rare, and origin and entity remain to be elucidated. A 51-year-old male presented with GP as a sessile polyp with smooth surface measured about 1cm in diameter in the descending portion of duodenum. Pathological examination displayed that a neoplasm was predominately located in submucosa and infiltrated mucosa focally. The tumor consisted of epithelioid, ganglion-like and spindle cells admixing in a haphazard way. The epithelioid cells resembled paraganglioma in cytological and architectural features. The ganglion-like cells were scattered and merged with the bland spindle cells in fascicular clusters, which resembled ganglioneuroma. Syn, MAP-2 and CgA were positive in the epithelioid and ganglion-like cells in variety and NF highlighted the ganglion-like cells. S-100 and SOX-10 were positive in the spindle cell proliferation as well as around the epithelioid cells. PR was positive in the epithelioid cells. The polyp was resected and no adjuvant therapy was given. The patient remained no recurrence in two years' follow-up. Origin of GP is presumed to be related with pancreas islet. GP is distinguished from NET G1 and designated as paraganglioma-ganglioneuroma, a kind of composite paragangliomas.